(3Jbhje GdCHOGf aj JOHjQ GdEfSGfs - (3jMji Hf YjSi Hf LRdI GdHZOGOj, CHh Ydj,J (B493 (3g` s
(3ChdgG (B:s
(3eHJhQI GdChd hChd GdehLhO efgG (B: (3gPG LgO Gdebd , aQJH JQJjHkG jSgd Ydi GdfGXQ ajg hJcKQ GdefaYI Hg , hjchf bdjd GdMLe cKjQ GdYde s
(3BNQgG (B:s
(3hai bGfhf GdJOHjQ GdUMjM Cf GdOhGA jfHZi Cf jhUd Edi GdYVh GdeOGhi ef CbQH GdehGVY Edjg s
(3fSNI NGeSIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B161 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B218s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B65 s
Keywords: (3GdWHs